(untitled) (European Bison Conservation Newsletter, 2008)
First European bison that appeared in Baligro´d Forest District in 1991 originated from the group released in 1980 at Wola Michowa, Komańcza Forest District. Since then, their numbers grew up, reaching about 120 in 2007. European bison are monitored there through direct and indirect (tracks, faeces, foraging signs etc.) observations. Monitored is also the health of animals through collection of faeces analysed for the presence of parasites, natural mortality, and the level of damages in forest stands – estimated so far as economically tolerable.